Clinicopathological Features of Thrombotic Microangiopathy in Renal Biopsies: A Retrospective Cross-sectional Study from Tertiary Care Centre in Kerala, India - Geethu G Nair; P Umasankar; Hijaz Poyyeri Thuvvakkod; Bindu C Sivasankaran; MK Thanooja (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: Thrombotic Microangiopathy (TMA) is a clinicopathological syndrome characterised by endothelial injury, microvascular thrombosis, and organ dysfunction. Renal involvement is common and may result from diverse primary and secondary aetiologies. The aetiological spectrum and histopathological manifestations of renal TMA vary considerably among different populations and clinical settings. Renal biopsy not only confirms the diagnosis but also provides valuable information regarding the pattern and chronicity of vascular and glomerular injury, which may have prognostic significance. Studies evaluating the spectrum of biopsy-proven renal TMA are limited, particularly from the Indian population, making such analyses important for improving diagnostic accuracy and patient management. Aim: To evaluate the clinicopathological features and aetiological spectrum of TMA in renal biopsies. Materials and Methods: This retrospective cross-sectional observational study was conducted in the Department of Pathology, Government Medical College, Kozhikode, Kerala, India and included all native and graft renal biopsies diagnosed with TMA between January 2020 and December 2024. Cases of Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis and biopsies lacking definitive histological features of TMA were excluded. Clinical parameters (age, sex, blood pressure, proteinuria, haematuria, renal function), laboratory parameters (haemoglobin, platelet count, serum creatinine, serum albumin, complement levels), and histopathological features were evaluated. Acute and chronic TMA lesions were assessed, and cases were categorised according to underlying aetiology. Data were entered into Microsoft Excel and analysed using descriptive statistics. Continuous variables were expressed as mean±standard deviation, while categorical variables were presented as frequencies and percentages. Results: Among 2,302 renal biopsies examined during the study period, 55 (2.4%) showed histological evidence of TMA. Forty-seven cases involved native kidneys and eight involved renal allografts. The mean age at presentation was 41.6±13.3 years, and 32.7% of patients were female. Hypertensionassociated TMA was the most common aetiology, accounting for 30 (54.55%) of cases, followed by transplant-associated TMA 8 (14.55%), IgA Nephropathy 7 (12.73%) autoimmune diseases 5 (9.09%), infection-related TMA 3 (5.45%), atypical haemolytic uraemic syndrome 1 (1.82%) and snake bite 1 (1.82%). All infection-related cases were associated with Coronavirus Disease-2019 (COVID-19). Proteinuria (89%) and microscopic haematuria (61.8%) were common clinical findings. Histologically, vascular lesions predominated, with fibrointimal hyperplasia and arteriolar thrombi being the most frequent abnormalities. Chronic vascular changes were more common than acute thrombotic lesions. Only two (3.64%) patients had thrombocytopenia, including the single case of complementmediated atypical Haemolytic Uraemic Syndrome (aHUS). Conclusion: Secondary causes predominate in renal TMA, with hypertension-associated TMA being the leading aetiology. Chronic vascular lesions are common and may reflect delayed presentation and sustained endothelial injury. Renal biopsy remains essential for diagnosis, aetiological classification, and identification of uncommon causes of TMA.